“As long as you learn to adapt”–a longitudinal mixed-methods study exploring the first decade with rheumatoid arthritis - Maria Bergström; Åsa Larsson Ranada; Annette Sverker; Ingrid Thyberg; Mathilda Björk (BMC Rheumatology)
Abstract Background Early diagnosis and modern treatment have changed everyday life of patients with rheumatoid arthritis (RA). However, symptoms are still pronounced several years after diagnosis. The aim of this study is therefore to synthesise the perception of everyday life in men and women with contemporary treated RA over the course of the first decade after diagnosis. This will be achieved by comparing subjective experiences with quantitative measures of disability and disease activity. Methods A longitudinal convergent mixed method was used. Thirty-one patients, clinically diagnosed with RA and ≥ 18 years of age, were recruited from the TIRA-2 project in southeast Sweden. Patients were followed over a decade regarding disease activity (DAS28), grip force (Grippit), pain intensity (VAS mm) and activity limitations (HAQ). Participation in valued life activities (VLA-swe) was assessed 10 years after diagnosis. The patients took part in individual interviews three- and ten-years post-diagnosis. Quantitative data were analysed through descriptive analyses and linear mixed models. The interviews were analysed using directed content analyses. The results from the quantitative and qualitative analyses were integrated in accordance with the chosen design. Results Discrepancies between the quantitative and qualitative results were revealed, along with differences between sexes. Women expressed more problems related to disease activity and grip force, which did not coincide with the quantitative results. In fact, women experienced difficulties in activities despite decreased disease activity. Furthermore, their pain score changed quantitatively over time, which was not expressed in the interviews. These disconfirming results were not seen in men. Both women and men displayed confirming results regarding activity limitation. Some issues, such as with basic needs, were more visible quantitatively than through interviews. Conclusions Men and women with contemporary treated RA still experience disability a decade after diagnosis. Additionally, patients’ experiences and quantitatively measured outcomes do not always coincide. The qualitative data adds information and thereby complements the quantitative data on disability. Our results confirm the importance of person-centred rehabilitation in optimising patients’ possibilities for participation in everyday life. Clinical trial number Not applicable.